Technical Support and Capacity Building for Mali-Meteo on ENACTS Tools and Products - Faniriantsoa, Rija; Dinh, Dannie; Dinku, Tufa (2025)
This report describes the technical support and capacity building activities on ENACTS tools and products provided by The International Research Institute for Climate and Society (IRI) at Columbia University for Mali National Meteorological Agency (Mali-Météo) in 2025.